Development of functional muffins enriched with lemon by-products as sources of Bioactive compounds - Ana Rita Soares Mateus; Angelina Pena; Ana Sanches Silva (Food Chemistry Advances)
Food waste is a growing global concern, and upcycling by-products from the food industry offers a sustainable solution. This study explores the incorporation of lemon by-products—fresh pomace, flour, and extract—into muffin formulations to enhance their nutritional, antioxidant, and sensory properties while reducing waste. While previous studies have separately explored the use of these lemon by-products, this work uniquely compares all three in a single context. Muffins enriched with lemon by-product flour showed lower lipid (9.97 %) and higher protein content (1.35 %), while those with fresh pomace had the highest fiber levels (6.55 %). Baking significantly increased antioxidant activity and total phenolic content due to the release of bound phenolics and the formation of Maillard reaction products. Sensory analysis revealed that muffins with fresh pomace and extract had the most appealing aroma, whereas those with flour scored lower due to the astringency of citrus peel components. Nonetheless, all formulations achieved high consumer acceptance, with muffins containing fresh pomace offering the best balance between nutritional and sensory qualities. This work highlights the influence of thermal processing on phenolic stability, showing reductions in flavonoids like rutin and naringenin during baking. The findings demonstrate that lemon by-products can be successfully incorporated into baked goods to create functional foods, supporting waste reduction and promoting a circular economy.